Distinct roles of myosin Va in membrane remodeling and exocytosis of secretory granules - Kögel, Tanja; Rudolf, Rüdiger; Hodneland, Erlend; Hellwig, Andrea; Kuznetsov, Sergei A.; Seiler, Florian; Söllner, Thomas; Barroso, João; Gerdes, Hans-Hermann (Traffic, 2010)
Hormone- and neuropeptide-containing secretory granules (SGs) of neuroendocrine PC12 cells are formed at the trans- Golgi network as immature SGs. These intermediates are converted to mature SGs in a complex maturation process, including matrix condensation, processing of cargo proteins and removal of proteins and membrane in clathrin-coated vesicles. The resulting mature SGs undergo Ca2+-dependent exocytosis upon an appropriate stimulus. We here show that the motor protein myosin Va is implicated in a maturation step of SGs, their binding to F-actin and their stimulated exocytosis. Interference with myosin Va function blocked the removal of the transmembrane protein furin from maturing SGs without affecting condensation and processing of proteins of the SG lumen. Furthermore, the ATP-inhibited binding of SGs to F-actin decreased with progressive maturation and upon interference with myosin Va function. Moreover, the expression of a dominant-negative myosin Va-tail or shRNA-based downregulation of myosin Va interfered with stimulated exocytosis of SGs. In summary, our data suggest an essential function of myosin Va in the membrane remodeling of SGs during maturation and a role in their exocytosis.
Gesehen am 16.03.2023